Consumer Protection Regarding Health Information and Warnings on Tobacco Cigarette Packaging - Anna Maria Tri Anggraini; Dian Purnamasari; Ahmad Sabirin; Dimas Ananta Putra; Jhon Rojell Y. Elizaga (Journal of Consumer Sciences, 2024)
Indonesia is one of the countries that has a cigarette community, it becomes a problem when the packaging on cigarettes does not provide accurate information, this certainly blames consumer protection. This study aims to delineate consumer protection measures regarding tobacco cigarette circulation without providing accurate information. Conducted in a normative framework. The findings suggest that legal protection for cigarette consumers who receive unclear or inaccurate information on cigarette product packaging can encompass preventive and repressive legal measures. Preventive measures are outlined in PP No. 109 of 2012 and PERMENKES No. 28 of 2013, specifically in Article 4 sub-articles c and i. Conversely, repressive measures enable individuals to file complaints with the Consumer Dispute Settlement Agency (known as BPSK) or initiate lawsuits. Furthermore, the responsibility of business actors to provide accurate information is underscored by Decision Number 32/Pid.B/2021/Pt. Pbr. This responsibility extends not only to distributors but also to cigarette manufacturers, such as PT. Leadon International, found in violation of various regulations, including Article 8 paragraph (1) sub-paragraphs a I, and j of the Godrej Consumer Products Limited (GCPL), in conjunction with Article 14 of Government Regulation Number 109 of 2012, and Article 10 paragraph (2) sub-paragraph a and paragraph (3) of PERMENKES No.28 of 2013. Sanctions for producers should adhere to Article 19, in conjunction with Article 62 paragraph (1) of the GCPL. At the same time, distributors face reprimands for product withdrawals as stipulated in Article 60 paragraph (3) of PP No. 109 of 2012.